Efektivitas Brain-Based Learning (BBL) terhadap Kemampuan Pemecahan Masalah Matematis Siswa: Systematic Literature Review - Meylani Eka Putri; Hasanuddin Hasanuddin (CV. Lentera Literasi Indonesia, 2026)
Mathematical problem-solving skills are the primary focus of this study, given students’ still-low ability to solve mathematical problems. One reason for this low proficiency is the prevalence of conventional teaching models, which do not sufficiently develop higher-order thinking skills. Brain-Based Learning (BBL) is a teaching model based on the brain’s processes of receiving and processing information, with the goal of maximizing student participation and understanding. This study employed a Systematic Literature Review (SLR) method in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The data were obtained from a search of scientific articles in the Google Scholar, Publish or Perish, OJS Jurnal, and Garuda databases. Ten articles were deemed eligible for analysis after undergoing a screening process based on inclusion and exclusion criteria and the PRISMA flowchart. The results of the study indicate that students’ ability to solve math problems at various educational levels is positively influenced by the systematic implementation of BBL. This improvement is evident in the ability to identify problems, formulate solutions, apply those solutions, and evaluate the results. Therefore, this study can serve as an empirical foundation for further, more in-depth research on the application of BBL in mathematics education.